Peningkatan Hasil Belajar Siswa Menggunakan Metode Card Sort Pada Pelajaran PAI Materi Zakat - Sumiati Isro (MGMP PAI SMP BINTAN, 2022)
This research was conducted to find out the reasons for the lack of students' interest and low value of student learning outcomes in participating in the learning process in the classroom, especially in the sixth grade elementary school students in learning Islamic Religious Education material Zakat. From the observations while the researchers saw that this was because the learning methods used by teachers were still conventional, students just sat quietly and observed the teacher's explanation of the material, without any direct experience. So that in this action research, one learning method is offered, namely Card Sort. The card sort method is a method in learning to teach concepts, classifying properties and facts about an object or information. This method is very interesting to be applied in PAI learning, so that students become active and motivated in learning activities. The results of data analysis on this study showed an increase in student learning activities and value of student learning outcomes in the subject of Islamic Religious Education with Zakat material.